Enlightened Piety during the Age of Benevolence: The Christian Knowledge Movement in the British Atlantic World - Roberson, Rusty (Church history, 2016)
By the 1690s, a religious initiative for benevolence and reform had taken firm hold throughout both England and Scotland. For roughly the next fifty years, a coherent movement for enlightened piety operated in the British Atlantic world that would emphasize institutional stability, social reform, and personal improvement. Constituting this movement were transatlantic religious networks that established unprecedented personal and institutional partnerships among traditionally antagonistic religious rivals. These collaborators sought to cultivate piety through traditional forms such as the enrichment of the liturgy, a refinement of architecture, and a fuller development of the faith through the application of the new learning to received revelation. Other efforts included prison reform alongside educational measures to promote Christian knowledge such as evangelism and missions, the teaching of the catechism, the circulation of libraries, and the establishment of charity schools. This was Britain's age of benevolence; at its core was a trans-denominational effort for spiritual renewal and social reform.